2010
DOI: 10.3109/15563650.2010.503657
|View full text |Cite
|
Sign up to set email alerts
|

Methemoglobinemia induced by indoxacarb intoxication

Abstract: Indoxacarb is a recently introduced insecticide whose mode of action is blockage of voltage-gated sodium channels. There are limited data on human ingestion. A case of 68-year-old healthy male who presented with general cyanosis because of methemoglobinemia following the ingestion of indoxacarb is presented. After receiving a methylene blue injection, the patient recovered without sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Indoxacarb is known to cause methemoglobinemia in humans through a series of accidental poisonings (Park, Kim et al 2011). Wu and colleagues published a case study of a 68-year old male with methemoglobinemia following ingestion of indoxacarb (Wu, Lin et al 2010), and Shih et al report a similar case (Shih and Tsai 2011). Jung et al review several similar case studies of indoxacarb-caused methemoglobinemia (Jung, Lee et al 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indoxacarb is known to cause methemoglobinemia in humans through a series of accidental poisonings (Park, Kim et al 2011). Wu and colleagues published a case study of a 68-year old male with methemoglobinemia following ingestion of indoxacarb (Wu, Lin et al 2010), and Shih et al report a similar case (Shih and Tsai 2011). Jung et al review several similar case studies of indoxacarb-caused methemoglobinemia (Jung, Lee et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…REG=regenerative; nonREG=non-regenerative; NEG=negative for anemia; MIX=both regenerative and non-regenerative studies. (Fujitani, Tada et al 1997, Fujitani, Tada et al 2000, Fujitani, Tada et al 2004 105512-06-9 Clodinafop-propargyl 3 nonREG nonREG NEG nonREG (Leet, Lindberg et al 2014) 1702 (Zhang, Cai et al 2002, Tchounwou, Patlolla et al 2003, Cheng, Li et al 2004 122-39-4 Diphenylamine 4 REG REG REG REG , Yoshida, Shimoji et al 1989 80844-07-1 (Wu, Lin et al 2010, Park, Kim et al 2011, Jung, Lee et al 2013, Leet, Lindberg et al 2014 77501-63-4 (Pinkhas, Djaldetti et al 1963) Judson et al Page 48 Comparison of predicted and experimental metabolite information…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Methemoglobinemia has been reported in a few cases of indoxacarb poisoning. [ 5 ] Unfortunately, equipment was not available to measure methemoglobin level in our center. However, symptoms of headache and lethargy, combined with the clinical findings of grayish cyanosis and the brown color of the phlebotomized blood, without significant cardiopulmonary dysfunction were strong enough to reach a diagnosis of methemoglobin and initiate therapy.…”
mentioning
confidence: 99%
“…1,2 Although there are many causes of methaemoglobinaemia, recently several authors have suggested that methaemoglobinaemia occurs after indoxacarb ingestion because its aromatic metabolites are biotransformed to active intermediates that produce methaemoglobin. 3,4 Methaemoglobin is an altered state of haemoglobin in which the ferrous (Fe 2+ ) ions of haem are oxidised to the ferric (Fe 3+ ) state. 5 Moderate to severe symptoms of methaemoglobinaemia might be treated with methylene blue.…”
mentioning
confidence: 99%
“…2). A case report by Wu et al 4 of a patient who ingested indoxacarb only required a single dose of methylene blue and the patient recovered without sequelae. This is one of the few case reports of indoxacarb poisoning that reports the duration of methaemoglobinaemia and administration of multiple doses of methylene blue.…”
mentioning
confidence: 99%